2003
DOI: 10.1111/j.1365-2788.2004.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric diagnosis in persons with intellectual disability in India

Abstract: Persons with ID do suffer from various psychiatric disorders. RSMB is a useful tool for differentiating between psychiatric problems and maladaptive behaviours. Hence RSMB can be used in the Indian context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…Considering the total prevalence of psychiatric diagnoses, our data are also consistent with those of other studies which found a lower prevalence of psychiatric disorders in participants with severeprofound intellectual disability compared with participants with mild or moderate intellectual disability [26,31]. According to Holden and Gitlesen [31], who used the Mini PAS-ADD to diagnose psychiatric disorders, these results reflect problems in detecting symptoms in persons with severe-profound intellectual disability, rather than a difference in prevalence of mental illness.…”
Section: S C H W E I Z E R a R C H I V F ü R N E U R O L O G I E U N supporting
confidence: 82%
See 1 more Smart Citation
“…Considering the total prevalence of psychiatric diagnoses, our data are also consistent with those of other studies which found a lower prevalence of psychiatric disorders in participants with severeprofound intellectual disability compared with participants with mild or moderate intellectual disability [26,31]. According to Holden and Gitlesen [31], who used the Mini PAS-ADD to diagnose psychiatric disorders, these results reflect problems in detecting symptoms in persons with severe-profound intellectual disability, rather than a difference in prevalence of mental illness.…”
Section: S C H W E I Z E R a R C H I V F ü R N E U R O L O G I E U N supporting
confidence: 82%
“…The reason for this difference may be explained by the fact that our population represents only a little part of the whole intellectual disability population in Geneva. Since challenging behaviour increases with severity of intellectual disability [26], we may have an overrepresentation of moderate and severe-profound intellectual disability levels, which leads to a dimi nution of the mild intellectual disability level prevalence. Indeed, besides intellectual disability, around 60% of the UPDM population has behaviour disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The predominance of ID in men seen in the Lundby cohort (63% vs. 37%) is well established knowledge (1,4,20), but conflicting results have been reported about the prevalence of mental disorder among mentally disabled males and females. Some authors report that mental disorder is more frequent among males than females with ID (21), whereas others do not find any difference between the genders (2).…”
Section: Risk Of Mental Disorder In Subjects With Idmentioning
confidence: 90%
“…The capacity to communicate is often very restricted and the individuals present other symptoms than those with mild or medium ID. Persons with severe ID will therefore to a less extent be diagnosed as having a mental disorder (5), making it difficult to tell if a real difference of the prevalence of mental disorder exists between mild, moderate and severe ID (6,20,21). Most previous studies have not adapted the diagnostic instruments according to verbal and other cognitive capacities making it difficult to interpret the results.…”
Section: Risk Of Mental Disorder In Subjects With Idmentioning
confidence: 95%
“…This condition of being dependent on others for routine decision-making on a daily basis largely diminishes their quality of life. The consequences for such lifelong confinement in institutions, due to their physical and/or cognitive limitations, are far beyond feelings of loneliness and anxiety; in many cases, people also suffer from mental illness (e.g., Kishore, Nizamie, Nizamie, & Jahan, 2004).…”
Section: Consequences Of Institutional Care and Education On Developmmentioning
confidence: 99%